Phylogeography of the Common Butterfly Lizard, Leiolepis belliana , Reveals Multiple Instances of Mitochondrial Introgression Driven by Historical Changes in River Systems - Nutthanun Khantasup; Amporn Wiwegweaw; Thongchai Ngamprasertwong; Jeren J. Gregory; L. Lee Grismer; Jesse L. Grismer; Nontivich Tandavanitj (Journal of Biogeography, 2026)
Aim To test the hypothesis that historical changes in Indochinese river systems shaped phylogeographic structure, diversification and hybridization events in butterfly lizards of the genus Leiolepis . Location Mainland Southeast Asia (Thailand, Cambodia, Vietnam and Peninsular Malaysia). Taxon Common butterfly lizard ( Leiolepis belliana ). Methods We analysed a multi‐locus dataset comprising one mitochondrial, NADH dehydrogenase subunit 2 ( ND2 ), and two nuclear genes, Exophilin 5 ( EXPH5 ) and Upstream transcription factor family member 3 ( USF3 ; KIAA2018 ), from samples spanning the distribution of Leiolepis belliana and other congeneric species within the genus Leiolepis . Phylogenetic relationships using both mitochondrial and nuclear genes were inferred using Maximum Likelihood and Bayesian Inference analyses. Divergence times were estimated, and ancestral range reconstructions were conducted using Statistical Dispersal‐Variance Analysis (S‐DIVA). Mitochondrial and nuclear DNA datasets were analysed separately to distinguish historical biogeographic patterns from signals of hybridization. Population genetic structure and demographic history were assessed using genetic diversity indices, a haplotype network, AMOVA and neutrality tests. Results The nuclear phylogenies suggested that Leiolepis belliana originated on the Thai–Malay Peninsula during the late Oligocene–early Miocene, followed by diversification across Central and Northern Thailand consistent with major reorganizations of the Mekong River system. In contrast, the mitochondrial phylogeny revealed contrasting relationships with the nuDNA dataset, indicating three independent instances of mitochondrial introgression involving other species within the genus Leiolepis . Divergence time estimations and ancestral area reconstructions collectively suggested that repeated shifts in river courses and sea‐level fluctuations transformed environmental barriers into areas of secondary contact and hybridization. Population genetic analyses further supported strong geographic structuring with different demographic signatures among populations. Main Conclusions The evolutionary history of L. belliana reflects a dynamic interplay between river system reorganizations and secondary contact. Indochinese river systems have not only promoted lineage divergence but also facilitated repeated hybridization in three different geographic areas subsequent to altering their courses and landscape connectivity. Integrating nuclear and mitochondrial evidence demonstrated how shifting river courses simultaneously drove diversification and introgression via hybridization, providing a framework for understanding the complex biogeographic patterns of Southeast Asian terrestrial biota.

Tooth microwear pattern variation in karst and non-karst peninsular Southeast Asian murine rodents - Sirikorn Sripho; Thongchai Ngamprasertwong; Alice Latinne; Serge Morand; Julien Claude (Mammal Research, 2024)

Spatial distribution of mitochondrial and microsatellite DNA variation in Daubenton's bat within Scotland - THONGCHAI NGAMPRASERTWONG; IAIN J. MACKIE; PAUL A. RACEY; STUART B. PIERTNEY (Molecular Ecology, 2008)
Daubenton's bat ( Myotis daubentonii ) is a known reservoir for European bat lyssavirus type 2 (EBLV‐2). An appreciation of the potential for epidemiological spread and disease risk requires an understanding of the dispersal of the primary host, and any large‐scale geographical barriers that may impede gene flow. The spatial pattern of microsatellite and mitochondrial DNA variation was examined to infer patterns of dispersal of bats among 35 populations across Scotland. DNA sequence variation at the mitochondrial control region and ND1 genes revealed two distinct phylogeographical clades, with generally nonoverlapping geographical distributions except for a small number of populations where both matrilines were found in sympatry. Such discontinuity suggests that Scotland was recolonised twice following the retreat of the Pleistocene ice sheet with little subsequent matrilineal introgression. However, eight microsatellite loci showed low levels of genetic divergence among populations, even between populations from the two distinct mitochondrial DNA clades. An overall, macrogeographical genetic isolation‐by‐distance pattern was observed, with high levels of gene flow among local populations. Apparently contrasting patterns of mitochondrial and microsatellite divergence at different scales could be explained by sex‐specific differences in gene flow at large scales.